Seeker - Rossi, Veronica (Riders, 2017)
After sealing Sebastian in a dark dimension with the demon Samrael, Daryl loses her visions and must rely on her instincts to lead the riders into a shadowy realm where she fears she may have to use evil powers in order to rescue him.